Target (Iris) Lesions of Erythema Multiforme - Rehman HU; Surtie F (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
A 21-month old age girl presented with asymptomatic lesions on her right arm of 4 days duration. She denied sore throat, fever and cough and no lesions were found anywhere else including buccal mucosa. She had not taken any medications recently.